KEPEMIMPINAN LOKAL, MODERASI BERAGAMA DAN PEMBANGUNAN BERKELANJUTAN DI PURWAKARTA - Kustini Kosasih; Moh Zaenal Abidin Eko Putro; Asnawati Mardamin (Balai Penelitian dan Pengembangan Agama Jakarta, 2021)
The Indonesian government remains continue to promote religious moderation because it is regarded as having strategic value to develop religious understanding for Indonesian people in religious realm. Research on religious moderation from the point of view of the texts is heavily undertaken. However, research on the social context of religious moderation by referring to social and state institutions has been less carried out. This article aims to describe the implementation of the concept of religious moderation which has been unwittingly launched by the local government of Purwakarta, West Java of Indonesia. By using a qualitative approach, this study explores the implement religious moderation in Purwakarta Regency through Dedi Mulyadi’s initiative in strengthening local culture, sustainable development, and institutonalizing religious moderation. The results of this study confirm that religious leaders as well as government leaders perceiving Dedi Mulyadi’s initiatives in strengthening local and cultural aspects in line with the spirit of sustainable development, let alone religious moderation.